Assessement of the effects and interactions of nitrates and salinity in Echinogammarus meridionalis, isolated and in mistures - Cruz, Beatriz Agostinho da (2018)
Freshwater ecosystems are among the world's most vulnerable ecosystems to climate change. These climatic changes have affected negatively the ecosystems, with the mean sea level rise leading to saline intrusion into freshwater ecosystems. Additionally, intensive agricultural practices and livestock production have been the cause of high concentrations of nitrates in groundwater and soil in various parts of the world. Due to these disturbances, namely in aquatic ecosystems, and imbalances, the variables salinity and nitrates were studied separately and combined (a more realistic scenario for ecosystems). The objective of this work was to evaluate the tolerance of Echinogammarus meridionalis to each of the selected variables seperately and in combination (mixture). The organisms were exposed to different concentrations for 96 hours. No food was given during the exposure period. Every day, mortality and physico-chemical parameters, such as conductivity, pH, oxygen saturation and temperature were recorded. At the end of each test, the organisms were separated into males and females and their body lengh measured. The LC50 of the acute toxicity tests for salinity was 25.38 ± 0.33 g L-1 and for the nitrate assays the LC50 resulting from the first collection of organisms was 121.59 ± 11.71 NO3-N L-1 and for the second collection the LC50 was of 116.99 ± 3.67 NO3-NL-1. The toxicity tests of the binary mixtures salinity and nitrate showed an antagonistic pattern at low concentrations in the S/A model (synergism /antagonism) and in the DL model (Dose Level deviation) there was antagonism at low concentrations and synergism at high concentrations. The results obtained in this work suggest a great tolerance to the salinity, hence it is expected that these Portuguese amphipods will be able to adapt to the climatic changes. Regarding nitrate tolerance, there was also a high resistance of the organisms in realistic concentrations and higher concentrations. The binary combinations of the mixture have an antagonistic effect at low concentration, thus suggesting a good adaptability of that organism to these environmental disturbances. When carrying out environmental biomonitoring studies in Portugal, it is useful to use native species rather than model species, since they play a crucial ecological role in the inherent ecosystem and the information obtained becomes more reliable and realistic.